2007
DOI: 10.7202/032973ar
|View full text |Cite
|
Sign up to set email alerts
|

Late Quaternary Sea Level Changes on Brock and Prince Patrick Islands, Western Canadian Arctic Archipelago

Abstract: Emerged shorelines are few and poorly defined on Prince Patrick and Brock islands. The sparse radiocarbon dates show emergence of only 10 m through the Holocene on the Arctic Ocean coast, increasing to 20 m 100 km to the east. Hence, from Brock Island, representative of westernmost coasts, the sea level curve since the latest Pleistocene has a very low gradient, whereas on eastern Prince Patrick Island the curve takes the more typical exponential form. A decline in isobases towards the west is thus registered.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 55 publications
1
6
0
Order By: Relevance
“…Our observations reinforce previously studies that reported submergence from adjacent parts of the westernmost Canadian Arctic Archipelago (CAA) (e.g., Hodgson et al, 1994;Forbes et al, 1986Forbes et al, , 2004Shaw et al, 1998). Furthermore, our observations provide independent support for recent geophysical modelling of relative sea-level change (RSL) in the western CAA that positions the modern zero isobase (separating land emergence to the east from submergence to the west) immediately east of Melville Island (Tarasov and Peltier, 2004).…”
Section: Introductionsupporting
confidence: 91%
See 2 more Smart Citations
“…Our observations reinforce previously studies that reported submergence from adjacent parts of the westernmost Canadian Arctic Archipelago (CAA) (e.g., Hodgson et al, 1994;Forbes et al, 1986Forbes et al, , 2004Shaw et al, 1998). Furthermore, our observations provide independent support for recent geophysical modelling of relative sea-level change (RSL) in the western CAA that positions the modern zero isobase (separating land emergence to the east from submergence to the west) immediately east of Melville Island (Tarasov and Peltier, 2004).…”
Section: Introductionsupporting
confidence: 91%
“…1). On southwestern Prince Patrick Island,~400 km west of Melville Island, Hodgson et al (1994) observed flooded river mouths, "ankledeep" submerged tundra surfaces as well as drowned beaches and barriers, all of which have been attributed to recent transgression. As with other sectors of the western Arctic where transgression-related coastal landforms have been observed, the recent transgression on Melville Island is driven mainly by the land subsidence due to peripheral forebulge collapse.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Ride-up involves fracturing but little deformation of the floating ice, whereas pile-up develops when frictional or compressive resistance leads to buckling failure that results in vertical growth of an ice Kovacs andSodhi, 1981, 1988). Landward motion of thick multiyear ice in the northwest Canadian Arctic Archipelago forms large shore ridges, primar ily, but not exclusively, on the outer Arctic coast (Figures 20(c) and 20(d)) (Hudson et al, 1981;Taylor and Hodgson, 1991;Forbes and Taylor, 1994;Hodgson et al, 1994). Onshore motion of ice produces grooved scour marks, push ridges and levees, mounds, cobble or boulder pavements, and boulder ramparts ( Figure 21) (Nichols, 1953;Hume and Schalk, 1964;Dionne, 1978Dionne, , 1985Dionne, , 1992Barnes, 1982;Hansom, 1983bHansom, , 1986Hansom, , 2005bForbes and Taylor, 1994).…”
Section: Polar Marine Processes: Sea Ice and Shore Icementioning
confidence: 99%
“…channels, terminating on the polar continental shelf. Deglaciation commenced ~11600 14 C years BP, and by 10 000 14 C years BP, prominent marine embayments extending from the Arctic Ocean had evacuated the Innuitian Ice Sheet from the inter-island channels of the western QEI (Hodgson et al, 1994;Atkinson, 2003;England et al, 2006). After 9000 14 C years BP, only island-based ice caps remained in the central and western QEI, although the Innuitian Ice Sheet remained contiguous between western Axel Heiberg Island and northwest Greenland (Lamoureux and England, 2000;Atkinson, 2003;England et al, 2004England et al, , 2006Fig.…”
mentioning
confidence: 99%